10th International Symposium on the Conservation of Monuments in the Mediterranean Basin Natural and Anthropogenic Hazards and Sustainable Preservation (Springer International Publishing, 2018)
This book addresses physical, chemical, and biological methods for the preservation of ancient artifacts. Advanced materials are required to preserve the Mediterranean belt's historic, artistic and archaeological relics against weathering, pollution, natural risks and anthropogenic hazards. Based upon the 10th International Symposium on the Conservation of Monuments in the Mediterranean Basin, this book provides a forum for international engineers, architects, archaeologists, conservators, geologists, art historians and scientists in the fields of physics, chemistry and biology to discuss principles, methods, and solutions for the preservation of global historical artifacts.